THE INFLUENCE OF SUPPORTIVE LEADERSHIP, TRUST AND RESPONSIBILITY ON THE PERFORMANCE OF SECTION CHIEF OF DISTRICT EDUCATION OFFICE IN JAKARTA - MUMKIN, IING AHMAD (Jurnal Ilmiah Educational Management, 2016)
The study is aimed at getting empirical evidences about direct and indirect influence of supportive leadership, trust and responsibility variables on the performance of Section Chief of District Education Office in Jakarta. Approach and method of this research is quantitative and descriptive correlation analysis with pathway analysis model. Simple random sampling is done to select 30 out of 42 Chiefs of District Education Office. The results showed that supportive leadership has positive direct influence on the performance, responsibility has positive direct influence on the performance, trust also has positive direct influence on performance. Supportive leadership has positive direct influence on responsibility, trust has direct positive influence on responsibility, and supportif leadership has direct positive influence on trust. In conclusion the three independent variables have direct positive influence on the performance.